Contraceptive Use Patterns Within Females’ First Sexual Relationships: The Role of Relationships, Partners, and Methods - Manlove, Jennifer (J Sex Res, 2007)
This study used the 1995 National Survey of Family Growth (NSFG) to assess whether characteristics offemales’sexual partners, relationships, and choice of contraceptive methods were associated with contraceptive use patterns within their first sexual relationship. White, Black, and Hispanic females under age 25 (N = 915) provided retrospective information on sexual activity and contraceptive use for first sexual relationships that occurred between 1991 and 1995. Females with older sexual partners and with same race/ethnicity partners (among Hispanics) had reduced odds of ever using contraception and/or uninterrupted use. Longer sexual relationships were associated with higher odds of ever using contraception but lower odds of uninterrupted use. Females who were older at first sex, who used hormonal methods (among Whites), or who switched to more effective methods during their first sexual relationships had higher odds of ever using contraception and/or uninterrupted use. In contrast, switching to less effective methods during a first sexual relationship was associated with reduced odds of uninterrupted use.